From Cavitation of Lung Metastases to Pneumothorax: An Amazing Response to Regorafenib in Metastatic Colorectal Cancer? A Case Report - Stefano, Alfonso De; Luca, Giuseppe De; Romano, Carmela; Piccirillo, Maria Carmela; Granata, Vincenza; Rocca, Antonello La; Avallone, Antonio (Archives of Clinical and Medical Case Reports, 2020)
Objective: In this case report, we describe a huge response of pulmonary lung lesions that resulted in a pneumothorax in a metastatic colorectal cancer patient treated with Regorafenib. Case Report: A 65-year-old woman, diagnosed with lung metastases from colon cancer began in the assumption of Regorafenib after failure of a prior line of chemotherapy. The disease was re-evaluated every two months by CT scan and a responding disease was reported, through the cavitation of all pulmonary nodules. Suddenly, after 9 months of a well-tolerated treatment, the patient showed cough, dyspnea and asthenia. She was admitted in our ward and a sub-massive pneumothorax was diagnosed and treated by thoracic surgeons by positioning a chest tube to get a normal expansion of the collapsed lung. Pneumothorax was solved, but patient discontinued Regorafenib as its positive activity on lung metastases, showing a deep response to treatment, was considered an adverse event that caused such a threatening side effect. Results: The pneumothorax was very probably caused by an excessive cavitation of lung sub-pleural nodules responding to chemotherapy extraordinarily. Conclusions: This case highlights the need to monitor constantly patients with lung metastases receiving regorafenib especially with subpleural localization for the consistent risk of such sequelae.